2015
DOI: 10.1186/s13014-015-0559-5
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive magnetic resonance imaging during brachytherapy for cervical carcinoma: predictive value of volume measurements with respect to persistent disease and prognosis

Abstract: BackgroundCervical cancer is associated with a high yearly mortality. The presence of persistent disease after radiotherapy is a significant predictor of patient survival.The aim of our study was to assess if tumor volume regression measured with MR imaging at the time of brachytherapy can discriminate between patients who eventually will achieve a complete response to radiotherapy from those who will not. The second objective was to evaluate whether tumor volume regression predicts overall treatment failure.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…According to the previous reports, tumor volume was calculated by multiplying the sum of tumor areas by the section thickness. 19 , 20 Tumor area was manually outlined on the sagittal or axial T2-weighted image images along the border of the each suspected tumor slice (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous reports, tumor volume was calculated by multiplying the sum of tumor areas by the section thickness. 19 , 20 Tumor area was manually outlined on the sagittal or axial T2-weighted image images along the border of the each suspected tumor slice (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further analysis revealed that the tumor size of the patients in the study by Vincens et al. (18) was much smaller (∼1 cm) than that of the patients in the other studies (16,17,20). This finding suggested that the size of the tumor in cervical cancer was a critical factor in the accuracy of MRI after BCT.…”
Section: Discussionmentioning
confidence: 67%
“…A careful analysis of all the studies revealed that the sensitivity, specificity, and accuracy (80%, 55.6%, and 64.3%, respectively) in the research by Vincens et al (18) were much lower than the corresponding values in the other three studies. Further analysis revealed that the tumor size of the patients in the study by Vincens et al (18) was much smaller ($1 cm) than that of the patients in the other studies (16,17,20). This finding suggested that the size of the tumor in cervical cancer was a critical factor in the accuracy of MRI after BCT.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations